Yield Dynamics of Mungbean (Vigna radiata L. Wilczek) Varieties in Poplar Based Agroforestry System - Pandey, Apurv; Tewari, Salil K. (Indian Journal of Agroforestry, 2020)
Evaluation of three mungbean cultivars was done under poplar and open with the effect of Rhizobium inoculation and fertilizer incorporation on yield and yield attributes. Experiment was laid out in Split-split plot design with three replications. Yield and yield contributing characters were found significantly higher in open condition than agroforestry. Pusa 9531 exhibited higher yield contributing characters and grain yield than Pusa 105 and Pant mung 2. Fertilizer treatment T4 (Fertilization along with Rhizobium inoculation) showed significantly higher magnitude in yield and yield attributes over other fertilizer treatments.